Trauma as a Theological Locus: Re-reading Muslim–Christian Relations in Indonesia through Trauma Theology - David Rade Manat Simanjuntak; Jekson Berdame; Ryanto Adilang; Heliyanti Kalintabu; Roy Kumowal (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This article examines post-conflict Muslim-Christian relations in Indonesia, using communal trauma as the primary unit of analysis. The aim of this study was to show how trauma functions as a relational reality that forms patterns of segregation, latent prejudice, and possible interfaith encounters. This study employs a qualitative approach through narrative inquiry, analyzing the documentary film Beta Mau Jumpa as a narrative-theological text, supported by a literature review on interreligious conflict and trauma theology. The results show that post-conflict trauma does not stop as an individual experience but operates as a collective memory that shapes Muslim-Christian relations in an ongoing manner. The novelty of this research lies in the positioning of trauma as a locus theologicus in the study of interreligious relations. This article contributes to the development of contextual theology and religious education by offering a more sensitive theological framework to the experience of wounds and post-conflict reconciliation.